2019
DOI: 10.1161/circinterventions.119.008110
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Outcomes at Time of Superior Cavopulmonary Connection Between Single Ventricle Patients With Ductal-Dependent Pulmonary Blood Flow Initially Palliated With Either Blalock-Taussig Shunt or Ductus Arteriosus Stent

Abstract: Background: Patients with single ventricle anatomy and ductal-dependent pulmonary blood flow may be initially palliated with either modified Blalock-Taussig shunt (BTS) or ductus arteriosus stent (DAS). Comparisons of outcomes during the interstage period and at the time of superior cavopulmonary connection (SCPC) are lacking and may differ between palliation strategies. Methods: Infants with single ventricle anatomy and ductal-dependent pulmonary blood… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 16 publications
1
10
0
Order By: Relevance
“…We acknowledge that our results may not be generalizable to centers that have excellent outcomes after SPS placement in single ventricle patients. For instance, our SPS patients experienced interstage mortality that was significantly higher than the 12.7% reported in a 2019 multicenter study by Meadows et al 16 To explain this difference, we first performed a critical review of our patient operative records which revealed no obvious technical issues. One possible contributing factor is poor adherence to anticoagulation in earlier SPS patients, although these data were not evaluated.…”
Section: Commentmentioning
confidence: 90%
See 3 more Smart Citations
“…We acknowledge that our results may not be generalizable to centers that have excellent outcomes after SPS placement in single ventricle patients. For instance, our SPS patients experienced interstage mortality that was significantly higher than the 12.7% reported in a 2019 multicenter study by Meadows et al 16 To explain this difference, we first performed a critical review of our patient operative records which revealed no obvious technical issues. One possible contributing factor is poor adherence to anticoagulation in earlier SPS patients, although these data were not evaluated.…”
Section: Commentmentioning
confidence: 90%
“…Similar trends are reported in other studies that assessed ECMO requirement. 12,16,23 Furthermore, of the nine SPS patients requiring ECMO, seven did not survive to S2P. This suggests that ECMO requirement following single ventricle palliation may be a predictor of interstage mortality.…”
Section: Commentmentioning
confidence: 99%
See 2 more Smart Citations
“…Notably, both strategies produced similar candidates for superior cavopulmonary connection, because preoperative hemodynamics and pulmonary artery growth did not differ. 4 These findings suggest greater nuance is needed when considering the source of pulmonary blood flow in patients with SV disease. Although not clearly associated with lower morbidity and mortality, DS would include patients with SV physiology who are more tenuous and less able to tolerate the stress of cardiopulmonary bypass and the risk of shunt thrombosis.…”
mentioning
confidence: 99%